A dose escalating, placebo controlled, double blind, single dose and multidose, safety and tolerability study of fontolizumab, a humanised anti-interferon γ antibody, in patients with moderate to severe Crohn's disease. Issue 8 (21st February 2006) - Reinisch, W; Hommes, D W; Van Assche, G; Colombel, J-F; Gendre, J-P; Oldenburg, B; Teml, A; Geboes, K; Ding, H; Zhang, L; Tang, M; Cheng, M; et al.
Abstract : Introduction: This study was designed to evaluate the safety of fontolizumab, a humanised anti-interferon γ antibody, in patients with moderate to severe Crohn's disease (CD). Patients and methods: Forty five patients with a CD activity index (CDAI) of 250–450 were randomised in a double blind, placebo controlled, dose escalating fashion to receive single doses of fontolizumab (0.1, 1.0, and 4.0 mg/kg) or placebo. By day 29, patients with clinical response were re-randomised to receive three additional doses of one half their initial fontolizumab dose or placebo at four weekly intervals. Primary objectives were safety and tolerability. Secondary outcomes included assessments of immunogenicity, clinical activity, and potential pharmacodynamic surrogates. Results: Treatment was generally well tolerated. There were slightly more reports of chills, flu-like syndrome, asthenia, nausea, and vomiting in the 1.0 mg and 4.0 mg/kg fontolizumab cohorts. Two serious adverse events rated as worsening of CD occurred under fontolizumab. Antibodies to fontolizumab were confirmed in one patient. No differences in clinical activity parameters were noted between any of the active treatment groups and placebo, with the placebo group having a particularly favourable outcome (60% response and 40% remission). By day 29, a more enhanced decrease in median Crohn's disease endoscopic index of severity (p = 0.02) and serum C reactive protein (p<0.001) was observed in the 4.0 mg/kg (n = 14) fontolizumab cohort compared with placebo (n = 10). Pharmacodynamic effects were observed by immunohistochemistry. Conclusions: Fontolizumab was well tolerated with minimal immunogenicity at doses of up to 4.0 mg/kg in patients with CD. A biological activity of fontolizumab is suggested.